Plant Growth Modelling:From Experimental Design to Modelling-TheArabidopsis Experiment*. Issue 7 (2016) - Dochain, D.; MacLean, H.
Abstract: This paper deals with the development and identification of a simple mass balance model for plant growth. Further to previous studies, this paper deals with modeling of growth of Arabidopsis thaliana, for which a detailed experimental design has been performed with the objective to address some of the limitations of the previously developed plant growth models, largely in terms of data availability, while accounting for the practical experimental constraints.